Pengaruh Perceived Quality, Brand Attachment dan Customer Satisfaction Terhadap Purchase Intention - Clarissa Chen (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
The purpose of this research is to examine the effect of Perceived Quality, Brand Attachment and Customer Satisfaction toward smartphone’s Purchase Intention in Jakarta. The population used for the research were users of smartphone domiciled in Jakarta. The sample size for this research were 150 smartphone users. Data used in this research are primary data obtained from online questionnaire and convenience sampling techniques was applied to collect all the data. The results of this research shows: 1. Perceived quality did not affects smartphone Purchase Intention in a positive way. 2. Brand Attachment affects smartphone Purchase Intention in a positive way. 3. Customer Satisfaction affects smartphone Purchase Intention in a positive way.